2016
DOI: 10.1103/physrevc.93.055501
|View full text |Cite
|
Sign up to set email alerts
|

Screening of nucleon electric dipole moments in nuclei

Abstract: A partial screening of nucleon electric dipole moments (EDMs) in nuclear systems, which is related to the Schiff mechanism known for neutral atomic systems, is discussed. It is shown that the direct contribution from the neutron EDM to the deuteron EDM is partially screened by about 1% in a zero-range approximation calculation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Here we repeat that the effect of the interaction between the nucleon EDM and the nuclear internal electric field [108] was not taken into account. This may suppress the nucleon EDM contribution to the nuclear EDM, although we do not evaluate it.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Here we repeat that the effect of the interaction between the nucleon EDM and the nuclear internal electric field [108] was not taken into account. This may suppress the nucleon EDM contribution to the nuclear EDM, although we do not evaluate it.…”
Section: Results and Analysismentioning
confidence: 99%
“…In nuclear systems, such enhancement is absent, since the system is nonrelativistic. Rather, it was recently suggested that the polarization of the nucleus due to the interaction between the EDM of the nucleon and the nuclear internal electric field can suppress the total intrinsic nucleon EDM contribution [108]. This phenomenon resembles the screening of the EDM of constituents in an electrically bound neutral system, first pointed out by Schiff [34].…”
Section: Calculation Of the Nuclear Edmmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, the nuclear spin matrix element cannot become larger than one for most of the stable nuclei, due to the strong pairing correlation. It has also recently been pointed that Schiff's screening, although being incomplete, may occur in nuclear systems [182]. The relative size between the nucleon EDM contribution and the polarization due to the CP-odd nuclear force will be discussed in the analysis.…”
Section: Electric Dipole Moments Of the Deuteron 3 H And 3 He Nucleimentioning
confidence: 96%
“…The data of the neutron EDM is also shown for comparison [24]. of nucleons may partially suppress the EDM of the nucleus, like the screening phenomenon of Schiff [28]. The nucleon EDM contribution is important for models of new physics which contribute through the quark EDM.…”
Section: Intrinsic Nucleon Edm Contributionmentioning
confidence: 96%